A comparison of catch phase force-time characteristics during clean derivatives from the knee - Comfort, P.; Williams, R.; Suchomel, T. J.; Lake, J. P. (The Journal of Strength and Conditioning Research, 2017)
The aim of this study was to compare load-absorption force-time characteristics of the clean from the knee (CK), power clean from the knee (PCK), and clean pull from the knee (CPK). Ten collegiate athletes (age 27.5 ± 4.2 years; height 180.4 ± 6.7 cm; mass 84.4 ± 7.8 kg) performed 3 repetitions each of the CK, PCK, and CPK with 90% of their 1 repetition maximum power clean on a force platform. The CK load-absorption duration (0.95 ± 0.35 seconds) was significantly longer compared with the CPK (0.44 ± 0.15 seconds; p < 0.001, d = 2.53), but not compared with the PCK (0.56 ± 0.11 seconds; p > 0.05, d = 1.08), with no differences between PCK and CPK (p > 0.05, d = 0.91). The CPK demonstrated the greatest mean force (2,039 ± 394 N), which was significantly greater than the PCK (1,771 ± 325 N; p = 0.012, d = 0.83), but not significantly different to the CK (1,830 ± 331 N; p > 0.05, d = 0.60); CK and PCK were not different (p > 0.05, d = 0.18). Significantly more load-absorption work was performed during the CK (655 ± 276 J) compared with the PCK (288 ± 109 J; d = 1.75, p < 0.001), but not compared with the CPK (518 ± 132 J; d = 0.80, p > 0.05). Additionally, more load-absorption work was performed during the CPK compared with the PCK (d = 1.90, p = 0.032). Inclusion of the catch phase during the CK does not provide any additional stimulus in terms of mean force or work during the load-absorption phase compared with the CPK, although the CPK may be beneficial in training rapid force absorption because of high force and a short duration.